TRA “SOLLICITATIO” E “DE PESSIMO”: CONTRIBUTO ALL’ANALISI STORICA DEGLI ABUSI SESSUALI CLERICALI NELLA CHIESA CATTOLICA (Glocalism: Journal of Culture, Politics and Innovation, 2025)
This article is dedicated to the analysis and review of documentation relating to sexual abuse by clergy, most of which is already known but has previously been presented in an incomplete manner. A comprehensive examination of these documents allows us to make some observations regarding the global management by the ecclesiastical institution of clerical sexual abuse in the Catholic Church in the 20th century, providing a different interpretative key and opening up further reflections from the point of view of theoretical and conceptual analysis.
Keywords: clerical sexual abuse; Holy Office; Catholic Church; sollicitatio; de pessimo